2019
DOI: 10.1111/ppa.13061
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatales associated with wounds on hardwood trees in Poland

Abstract: Wounds on trees provide entrance for many members of the Ophiostomatales (Ascomycota), including economically damaging tree pathogens. Because very little is known regarding wound‐associated fungi on hardwoods in Europe or their potential nitidulid beetle vectors (Coleoptera), the aim of this survey was to explore the diversity of these fungi in Poland. Wound samples associated with 26 tree species were collected from 18 stands in Poland. Fungi belonging to the Ophiostomatales were isolated and identified base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The results of the present study and other Polish findings (Jankowiak et al 2019a) indicated that C. synnemata and L. alneum have been found only occasionally from other beetle species and therefore can be considered as regular and possible specific associates of D. alni. Leptographium piriforme is less specific and can be found with other beetle species (Jankowiak and Kolařík 2010) or hardwood wounds (Jankowiak et al 2019c) in low numbers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of the present study and other Polish findings (Jankowiak et al 2019a) indicated that C. synnemata and L. alneum have been found only occasionally from other beetle species and therefore can be considered as regular and possible specific associates of D. alni. Leptographium piriforme is less specific and can be found with other beetle species (Jankowiak and Kolařík 2010) or hardwood wounds (Jankowiak et al 2019c) in low numbers.…”
Section: Discussionmentioning
confidence: 97%
“…However, the results of the present study confirm previous Polish investigations that some of the Leptographium species have a close affinity to hardwoods in Europe. Recently, L. betulae, L. tardum, and L. trypodendri were collected from hardwood-infesting bark beetles in Poland (Jankowiak et al 2017(Jankowiak et al , 2018, while three other Leptographium species have been isolated and formally described from hardwood wounds (Jankowiak et al 2018(Jankowiak et al , 2019c.…”
Section: Discussionmentioning
confidence: 99%
“…Neosetophoma clematidis occurred on the branches of Clematis vitalba L. [ 53 ] and Niesslia mucida on the bark of diverse plants, especially conifers [ 54 ]. Ophiostomataceae have been associated with wounds on hardwood trees in Poland [ 55 ]. Phaeoacremonium species occurred on European olive, quince and willow [ 27 ]; Phialocephala on rotten deciduous wood [ 56 ]; Phoma on the decaying wood of oak and pine [ 57 ]; Plagiostoma in the stems, twigs, and branches of woody and herbaceous plants from a wide range of plants in temperate regions of the Northern Hemisphere [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The collection details for the isolates included in the present study (Table 1) are provided in previous studies (Jankowiak et al 2019a(Jankowiak et al , 2019b(Jankowiak et al , 2019c. The cultures are maintained in the culture collection of the Department of Forest Ecosystems Protection, University of Agriculture in Krakow, Poland, and in the culture collection of the Natural Resources Institute Finland (Luke), Helsinki, Finland.…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…Jankowiak et al (2019a) conducted the first extensive survey of fungal associates of hardwood-infesting bark and ambrosia beetles in Poland. In the same year, Ophiostomatales associated with wounds on hardwood trees were also studied in Poland (Jankowiak et al 2019b). These studies reported several Sporothrix species, which were apparently new to science, but names were not provided for them.…”
Section: Introductionmentioning
confidence: 99%